Basic characteristics of plasma rich in growth factors (PRGF): blood cell components and biological effects. Issue 2 (18th March 2016) - Nishiyama, Kazuhiko; Okudera, Toshimitsu; Watanabe, Taisuke; Isobe, Kazushige; Suzuki, Masashi; Masuki, Hideo; Okudera, Hajime; Uematsu, Kohya; Nakata, Koh; Kawase, Tomoyuki
Abstract: Platelet‐rich plasma (PRP) is widely used in regenerative medicine because of its high concentrations of various growth factors and platelets. However, the distribution of blood cell components has not been investigated in either PRP or other PRP derivatives. In this study, we focused on plasma rich in growth factors (PRGF), a PRP derivative, and analyzed the distributions of platelets and white blood cells (WBCs). Peripheral blood samples were collected from healthy volunteers ( N = 14) and centrifuged to prepare PRGF and PRP. Blood cells were counted using an automated hematology analyzer. The effects of PRP and PRGF preparations on cell proliferation were determined using human periosteal cells. In the PRGF preparations, both red blood cells and WBCs were almost completely eliminated, and platelets were concentrated by 2.84‐fold, whereas in the PRP preparations, both platelets and WBCs were similarly concentrated by 8.79‐ and 5.51‐fold, respectively. Platelet counts in the PRGF preparations were positively correlated with platelet counts in the whole blood samples, while the platelet concentration rate was negatively correlated with red blood cell counts in the whole blood samples. In contrast, platelet counts and concentration rates in the PRP preparations were significantly influenced by WBC counts in whole blood samples. The PRP preparations, but not the PRGF preparations, significantly suppressed cell growth at higher doses in vitro. Therefore, these results suggest that PRGF preparations can clearly be distinguished from PRP preparations by both inclusion of WBCs and dose‐dependent stimulation of periosteal cell proliferation in vitro.